Sustainable Management of Keratin Waste Biomass: Applications and Future Perspectives - Sharma,Swati (2016)
Keratin is a durable, fibrous protein which is mainly present in higher vertebrates (mammals, birds and reptiles) and humans epithelial cells. Food industry especially the meat market, slaughter house and wool industry produces million of tons of keratin containing biomass. These industries are constantly growing and the major producers include USA, Brazil and China, account for more than 40 million tons per year. These proteins constitute keratin by-products have from 15 to 18% nitrogen, 2-5% sulphur, 3.20% mineral elements and 1.27% fat and 90% of proteins. The organic waste rich in keratin can be utilized as a natural source using chemical and mechanical methods. The natural keratin obtained by biomass does not contain any harmful chemical and can be used directly to produce variety of cosmetics, creams, shampoos, hair conditioners and biomedical products. The natural protein is more compatible to use or apply on human skin and hairs. The monomeric units of natural keratin can penetrate in the skin and hair cuticle and able to nourish the skin without any side effects. In the present review various strategies for the purification and separation of keratin from the organic waste have been described and use of natural keratin in cosmetics and pharmaceutical industry has also been explored.